Peculiarities of Adaptation of Albanian and Latin American Students to a Foreign Environment - A Aliajdaraj; A Costales (Peoples' Friendship University of Russia (RUDN University), 2011)
The intercultural adaptation is analyzed in the article, disclosing the acute specifics of the structure of the adaptation of Albanian and Latin American students during the time of living in Moscow.